Basic Mechanisms of Immunometabolites in Shaping the Immune Response - Dylan Gerard Ryan; Christian Graham Peace; Alexander Hooftman (Journal of Innate Immunity, 2023)
Background: Innate immune cells play a crucial role in responding to microbial infections, but their improper activation can also drive inflammatory disease. For this reason, their activation state is governed by a multitude of factors, including the metabolic state of the cell and, more specifically, the individual metabolites which accumulate intracellularly and extracellularly. This relationship is bidirectional, as innate immune cell activation by pathogen-associated molecular patterns causes critical changes in cellular metabolism. Summary: In this review, we describe the emergence of various “immunometabolites.” We outline the general characteristics of these immunometabolites, the conditions under which they accumulate, and their subsequent impact on immune cells. We delve into well-studied metabolites of recent years, such as succinate and itaconate, as well as newly emerging immunometabolites, such as methylglyoxal. Key Messages: We hope that this review may be used as a framework for further studies dissecting the mechanisms by which immunometabolites regulate the immune system and provide an outlook to harnessing these mechanisms in the treatment of inflammatory diseases.